Preparation method and application of low-expansion silicon-carbon negative electrode material
By doping nanometallic particles in porous silicon and wrapping them in the shell formed by a carbon source, the problem of large volume changes in pure silicon negative electrode materials during charging and discharging is solved, the first Coulomb efficiency and mechanical strength are improved, capacity attenuation is reduced, and production costs are reduced.
Patent Information
- Application Number
- CN202510097150.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The volume of pure silicon negative electrode material changes greatly during charging and discharging, resulting in repeated SEI rupture, low cycle life, irreversible Li consumption and low capacity performance in actual applications, hindering its application in all batteries.
By doping nanometallic particles in porous silicon and wrapping them in a shell formed by a carbon source, the transmission path of electrons and ions is optimized, local expansion is reduced, and mechanical strength and structural stability are improved.
It effectively alleviates the local expansion of porous silicon, improves the first Coulomb efficiency, reduces capacity attenuation during the cycle, and reduces production costs.
Smart Images

Figure CN119528146A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a preparation method and application of a low-expansion silicon-carbon negative electrode material. Background Art
[0002] One of the development directions of lithium-ion batteries is higher energy density, and developing new electrode materials is an effective means to improve energy density. As for negative electrode materials, the actual capacity of graphite currently widely used in commercialization is close to its theoretical capacity. Therefore, it is necessary to develop new high-capacity negative electrode materials to further improve the energy density of batteries.
[0003] Among all the new negative electrode materials, pure silicon negative electrode materials are considered to be the most promising next-generation negative electrode materials due to their high theoretical specific capacity, low redox potential, abundant reserves and environmental friendliness. However, the huge volume change (over 300%) during the charge and discharge process brought about by the high capacity and the low electronic and ionic conductivity and other characteristics have led to many problems such as repeated SEI rupture, low cycle life, irreversible Li consumption, and low capacity utilization in actual applications, which seriously hinder the application of pure silicon negative electrode materials in full batteries. In addition, a large number of micropores below 1nm will cause porous carbon to have too high a specific surface area, which will reduce the initial efficiency when preparing silicon-carbon negative electrode materials. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a low-expansion silicon-carbon negative electrode material. The doping of nano-metal particles effectively alleviates the local expansion of porous silicon. The carbon source wraps the nano-metal-doped porous silicon, effectively alleviating the expansion of porous silicon and improving the first-round coulomb efficiency.
[0005] To achieve the above object, the present invention provides a method for preparing a low expansion silicon-carbon negative electrode material, comprising the following steps: S1. Pre-treat silicon particles in piranha solution, then wash with deionized water until neutral, evenly sprinkle magnesium powder on the surface after drying, heat at 800-1200°C for 1-5h, wash after cooling to room temperature, and blow dry with nitrogen to obtain porous silicon; S2, mixing the nano-metal mixed suspension and the porous silicon in S1, ultrasonicating the mixture, collecting the solid by centrifugation, washing the solid, and drying the solid to obtain the nano-metal doped porous silicon; S3, mixing the nano-metal-doped porous silicon obtained in S2 with the carbon source, grinding the mixture, drying the mixture, placing the mixture in a tube furnace, and pyrolyzing the mixture under an inert atmosphere to obtain a pyrolysis product; S4. The pyrolysis product in S3 is mixed with polyvinyl pyrrolidone and then ground. The mixture is then placed in a tubular furnace, heated under an inert atmosphere, and cooled to obtain a silicon-carbon negative electrode material.
[0006] Preferably, in S1, concentrated hydrochloric acid and deionized water are used sequentially for washing 2-5 times.
[0007] Preferably, in S2, the drying is performed at 70-90° C. for 8-12 h.
[0008] Preferably, in S2, the nanometal in the nanometal mixed suspension includes one or more of nanoantimony, nanotin, nanotitanium, nanoaluminum and nanoiron.
[0009] Preferably, in S2, the grinding is carried out under the protection of an inert atmosphere, the grinding speed is 500-1200 rpm / min, and the grinding time is 1-8 h.
[0010] Preferably, in S3, the carbon source includes one or more of cyclodextrin, graphene, asphalt, carbon nanotubes, biomass carbon and polystyrene.
[0011] Preferably, in S3, the pyrolysis temperature is 800-1200° C. and the time is 1-5 h.
[0012] Preferably, in S4, the mass ratio of the pyrolysis product to polyvinyl pyrrolidone is 5-12:1.
[0013] Preferably, in S4, heating is performed at 1200-1800° C. and the temperature is maintained for 2-5 hours.
[0014] An application of a low-expansion silicon-carbon negative electrode material. The silicon-carbon negative electrode material prepared by the above preparation method is applied to the negative electrode of a lithium battery.
[0015] Therefore, the present invention adopts the above-mentioned method for preparing a low expansion silicon-carbon negative electrode material and its application, and its beneficial effects are: 1. In the silicon-carbon negative electrode material provided by the present invention, nano-metal particles are doped into porous silicon to optimize the transmission path of electrons and ions. The nano-metal particles provide mechanical support to the porous silicon to enhance the mechanical strength and structural stability of the porous silicon, reduce the capacity attenuation during the cycle, and the porous silicon structure is conducive to the penetration of the electrolyte; 2. In the silicon-carbon negative electrode material provided by the present invention, the carbon source material forms a shell to wrap the nano-metal-doped porous silicon inside, and the cyclodextrin on the carbon shell reacts with polyvinyl pyrrolidone. The cyclodextrin makes the polyvinyl pyrrolidone evenly distributed on the surface of the silicon-carbon negative electrode and partially wraps the pore size of the silicon-carbon negative electrode, thereby adjusting the pores of the silicon-carbon negative electrode material and improving the first coulomb efficiency; 3. The nano-metal particles used in the present invention can act as a buffer layer to absorb and disperse the stress generated by the expansion of porous silicon, and form a conductive network to improve the transmission path of ions and reduce the phenomenon of local expansion; 4. The present invention reduces production costs by using carbon sources such as biochar.
[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the XRD diagram of the silicon-carbon negative electrode, Si and β-cyclodextrin in Example 4 of the present invention; Figure 2 It is the first-round charge and discharge curve diagram of Application Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0018] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the usual meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features mentioned in the present invention or the features mentioned in the specific examples can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0019] Example 1 S1. Pretreat the silicon particles in piranha solution (3:1, V / V, concentrated sulfuric acid: hydrogen peroxide) for 1 h, then wash with deionized water until neutral, sprinkle magnesium powder evenly on the surface after drying, heat at 1000°C for 1.5 h, cool to room temperature and then wash, wash with concentrated hydrochloric acid and deionized water in turn, wash 5 times, and blow dry with nitrogen to obtain porous silicon.
[0020] S2. The nanometal mixed suspension (nanoantimony and nanotin mixed in a mass ratio of 1:1) and the porous silicon in S1 are mixed and sonicated, and the solid is collected after centrifugation. The solid is washed alternately with ethanol and deionized water, and dried at 80°C for 9h to obtain nanometal-doped porous silicon with a nanometal doping amount of 10%.
[0021] S3. The nano-metal-doped porous silicon and carbon source (β-cyclodextrin and biomass carbon mixed in a mass ratio of 1:2) obtained in S2 are mixed in a mass ratio of 1:3 and ground. After drying, they are placed in a tubular furnace and pyrolyzed under an inert atmosphere at a pyrolysis temperature of 1200°C for 2 hours to obtain a pyrolysis product.
[0022] S4. The pyrolysis product in S3 was mixed with polyvinyl pyrrolidone in a mass ratio of 10:1 and ground at 500 rpm / min for 10 h. The mixture was then placed in a tubular furnace and kept at 1500° C. for 3 h under an inert atmosphere. After cooling, a silicon-carbon negative electrode material was obtained.
[0023] Example 2 S1. Pretreat the silicon particles in piranha solution (3:1, V / V, concentrated sulfuric acid: hydrogen peroxide) for 1 h, then wash with deionized water until neutral, sprinkle magnesium powder evenly on the surface after drying, heat at 1000°C for 1.5 h, cool to room temperature and then wash, wash with concentrated hydrochloric acid and deionized water in turn, wash 5 times, and blow dry with nitrogen to obtain porous silicon.
[0024] S2. The nanometal mixed suspension (nanotin and nanotitanium mixed in a mass ratio of 1:1) and the porous silicon in S1 are mixed and sonicated, and the solid is collected after centrifugation. The solid is washed alternately with ethanol and deionized water, and dried at 70°C for 12h to obtain nanometal-doped porous silicon with a nanometal doping amount of 12%.
[0025] S3. The nano-metal-doped porous silicon and carbon source (β-cyclodextrin and asphalt mixed in a mass ratio of 1:2) obtained in S2 are mixed in a mass ratio of 1:2 and ground. After drying, they are placed in a tubular furnace and pyrolyzed under an inert atmosphere at a pyrolysis temperature of 1200°C for 2 hours to obtain a pyrolysis product.
[0026] S4. The pyrolysis product in S3 was mixed with polyvinyl pyrrolidone in a mass ratio of 10:1 and ground at 500 rpm / min for 10 h. The mixture was then placed in a tubular furnace and kept at 1500° C. for 3 h under an inert atmosphere. After cooling, a silicon-carbon negative electrode material was obtained.
[0027] Example 3 S1. Pretreat the silicon particles in piranha solution (3:1, V / V, concentrated sulfuric acid: hydrogen peroxide) for 1 h, then wash with deionized water until neutral, sprinkle magnesium powder evenly on the surface after drying, heat at 1000°C for 1.5 h, cool to room temperature and then wash, wash with concentrated hydrochloric acid and deionized water in turn, wash 5 times, and blow dry with nitrogen to obtain porous silicon.
[0028] S2. The nanometal mixed suspension (nano-titanium and nano-aluminum mixed in a mass ratio of 3:1) and the porous silicon in S1 are mixed and sonicated, and the solid is collected after centrifugation. The solid is washed alternately with ethanol and deionized water, and dried at 90°C for 8h to obtain nanometal-doped porous silicon with a nanometal doping amount of 15%.
[0029] S3. The nano-metal-doped porous silicon and carbon source (β-cyclodextrin and graphene mixed in a mass ratio of 1:2) obtained in S2 are mixed in a mass ratio of 1:3 and ground. After drying, the mixture is placed in a tubular furnace and pyrolyzed under an inert atmosphere at a pyrolysis temperature of 1200° C. for 2 h to obtain a pyrolysis product.
[0030] S4. The pyrolysis product in S3 was mixed with polyvinyl pyrrolidone in a mass ratio of 10:1 and ground at 500 rpm / min for 10 hours. The mixture was then placed in a tubular furnace and kept at 1500° C. for 3 hours under an inert atmosphere. After cooling, a silicon-carbon negative electrode material was obtained.
[0031] Example 4 S1. Pretreat the silicon particles in piranha solution (3:1, V / V, concentrated sulfuric acid: hydrogen peroxide) for 1 h, then wash with deionized water until neutral, sprinkle magnesium powder evenly on the surface after drying, heat at 1000°C for 1.5 h, cool to room temperature and then wash, wash with concentrated hydrochloric acid and deionized water in turn, wash 5 times, and blow dry with nitrogen to obtain porous silicon.
[0032] S2. The nanometal mixed suspension (nanoantimony and nanotitanium mixed in a mass ratio of 1:2) and the porous silicon in S1 are mixed and sonicated, and the solid is collected after centrifugation. The solid is washed alternately with ethanol and deionized water, and dried at 80°C for 10 h to obtain nanometal-doped porous silicon with a nanometal doping amount of 18%.
[0033] S3. The nano-metal-doped porous silicon and carbon source (β-cyclodextrin and carbon nanotubes mixed in a mass ratio of 1:2) obtained in S2 are mixed in a mass ratio of 1:2 and ground. After drying, they are placed in a tubular furnace and pyrolyzed under an inert atmosphere at a pyrolysis temperature of 1200°C for 2 hours to obtain a pyrolysis product.
[0034] S4. The pyrolysis product in S3 was mixed with polyvinyl pyrrolidone in a mass ratio of 10:1 and ground at 500 rpm / min for 10 h. The mixture was then placed in a tubular furnace and kept at 1500° C. for 3 h under an inert atmosphere. After cooling, a silicon-carbon negative electrode material was obtained.
[0035] Example 5 S1. Pretreat the silicon particles in piranha solution (3:1, V / V, concentrated sulfuric acid: hydrogen peroxide) for 1 h, then wash with deionized water until neutral, sprinkle magnesium powder evenly on the surface after drying, heat at 1000°C for 1.5 h, cool to room temperature and then wash, wash with concentrated hydrochloric acid and deionized water in turn, wash 5 times, and blow dry with nitrogen to obtain porous silicon.
[0036] S2. The nanometal mixed suspension (nanotin and nanoiron mixed in a mass ratio of 1:1.5) and the porous silicon in S1 are mixed and sonicated, and the solid is collected after centrifugation. The solid is washed alternately with ethanol and deionized water, and dried at 70°C for 12 hours to obtain nanometal-doped porous silicon with a nanometal doping amount of 20%.
[0037] S3. The nano-metal-doped porous silicon and carbon source (β-cyclodextrin and polystyrene mixed in a mass ratio of 1:2) obtained in S2 are mixed in a mass ratio of 1:3 and ground. After drying, they are placed in a tubular furnace and pyrolyzed under an inert atmosphere at a pyrolysis temperature of 1200° C. for 2 h to obtain a pyrolysis product.
[0038] S4. The pyrolysis product in S3 was mixed with polyvinyl pyrrolidone in a mass ratio of 10:1 and then ground. The mixture was then placed in a tubular furnace and kept at 1500° C. for 3 h under an inert atmosphere. After cooling, a silicon-carbon negative electrode material was obtained.
[0039] Application Example 1 The silicon-carbon negative electrode material in Example 2 is mixed with a binder, carbon black and a solvent to obtain a negative electrode slurry, the negative electrode slurry is coated on a copper foil current collector to obtain a negative electrode sheet, and then the negative electrode sheet is prepared together with a positive electrode sheet, a separator and an electrolyte to obtain a lithium-ion battery.
[0040] Comparative Example 1 S1. Pretreat the silicon particles in piranha solution (3:1, V / V, concentrated sulfuric acid: hydrogen peroxide) for 1 h, then wash with deionized water until neutral, sprinkle magnesium powder evenly on the surface after drying, heat at 1000°C for 1.5 h, cool to room temperature and then wash, wash with concentrated hydrochloric acid and deionized water in turn, wash 5 times, and blow dry with nitrogen to obtain porous silicon.
[0041] S2. The porous silicon obtained in S1 and the carbon source (β-cyclodextrin and asphalt mixed in a mass ratio of 1:2) are mixed and ground. After drying, they are placed in a tubular furnace and pyrolyzed under an inert atmosphere at a pyrolysis temperature of 1200°C for 2 hours. After cooling, a silicon-carbon negative electrode material is obtained.
[0042] According to the method in Application Example 1, a lithium ion battery was prepared using the silicon-carbon negative electrode material in Comparative Example 1.
[0043] Comparative Example 2 S1. Pretreat the silicon particles in piranha solution (3:1, V / V, concentrated sulfuric acid: hydrogen peroxide) for 1 h, then wash with deionized water until neutral, sprinkle magnesium powder evenly on the surface after drying, heat at 1000°C for 1.5 h, cool to room temperature and then wash, wash with concentrated hydrochloric acid and deionized water in turn, wash 5 times, and blow dry with nitrogen to obtain porous silicon.
[0044] S2. The porous silicon and carbon source asphalt obtained in S1 are mixed and ground, dried and placed in a tubular furnace for pyrolysis under an inert atmosphere at a pyrolysis temperature of 1200° C. for 2 h to obtain a pyrolysis product.
[0045] S3. The pyrolysis product in S2 was mixed with polyvinyl pyrrolidone in a mass ratio of 10:1 and then ground. The mixture was then placed in a tubular furnace and kept at 1500° C. for 3 h under an inert atmosphere. After cooling, a silicon-carbon negative electrode material was obtained.
[0046] Test Case a. The batteries assembled in Application Example 1 and Comparative Example 1 were subjected to charge and discharge tests on a LAND charge and discharge tester.
[0047] Cyclic tests were conducted at a charge and discharge rate of 0.2C (1C=1600mA / g) in the voltage range of 0.005-1.5V. The first cycle discharge capacity was 2857.0mAh / g, the first coulomb efficiency was 90.3%, and the discharge capacity retention rate after 500 cycles was 91.0%.
[0048] The battery assembled in Comparative Example 1 was subjected to charge and discharge tests on a LAND charge and discharge tester. Cycle tests were performed at a charge and discharge rate of 0.2C (1C=1600mA / g) in the voltage range of 0.005-1.5V. The first cycle discharge capacity was 2552.0mAh / g, the first coulomb efficiency was 78.3%, and the discharge capacity retention rate after 500 cycles was 72.4%.
[0049] From the comparison of the data of comparative example 1 and application example 1, it can be seen that the first coulombic efficiency of application example 1 is significantly improved, indicating that polyvinyl pyrrolidone can effectively improve the first coulombic efficiency by adjusting the pores on the carbon coating layer.
[0050] b. XRD test was performed on the silicon-carbon negative electrode material obtained in Example 4. The results are as follows Figure 1 As shown, it can be seen that the silicon-carbon negative electrode material in Example 4 shows characteristic peaks of silicon near 29°, 48° and 57°, and a characteristic peak of the carbon coating layer appears near 20°, indicating the successful synthesis of the silicon-carbon negative electrode material.
[0051] c. Corresponding to Example 1 and Comparative Example 1 at 0.1Ag -1 The first round of charge and discharge tests were carried out at a current density of Figure 2 shown.
[0052] Therefore, the present invention adopts a method for preparing and applying a low-expansion silicon-carbon negative electrode material using the above steps. The doping of nano-metal particles effectively alleviates the local expansion of porous silicon, and the carbon source wraps the nano-metal-doped porous silicon, effectively alleviating the expansion of porous silicon.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a low expansion silicon-carbon negative electrode material, characterized in that: The following steps are included: S1. Pre-treat silicon particles in piranha solution, then wash with deionized water until neutral, evenly sprinkle magnesium powder on the surface after drying, heat at 800-1200°C for 1-5h, wash after cooling to room temperature, and blow dry with nitrogen to obtain porous silicon; S2, mixing the nano-metal mixed suspension and the porous silicon in S1, ultrasonicating the mixture, collecting the solid by centrifugation, washing the solid, and drying the solid to obtain the nano-metal doped porous silicon; S3, mixing the nano-metal-doped porous silicon obtained in S2 with the carbon source, grinding the mixture, drying the mixture, placing the mixture in a tube furnace, and pyrolyzing the mixture under an inert atmosphere to obtain a pyrolysis product; S4. The pyrolysis product in S3 is mixed with polyvinyl pyrrolidone and then ground. The mixture is then placed in a tubular furnace, heated under an inert atmosphere, and cooled to obtain a silicon-carbon negative electrode material.
2. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S1, concentrated hydrochloric acid and deionized water are used in sequence for washing 2-5 times.
3. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S2, the drying step is performed at 70-90° C. for 8-12 h.
4. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S2, the nanometal in the nanometal suspension includes one or more of nanoantimony, nanotin, nanotitanium, nanoaluminum and nanoiron.
5. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S2, grinding is carried out under the protection of an inert atmosphere, the grinding speed is 500-1200 rpm / min, and the grinding time is 1-8 h.
6. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S3, the carbon source includes one or more of cyclodextrin, graphene, asphalt, carbon nanotubes, biomass carbon and polystyrene.
7. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S3, the pyrolysis temperature is 800-1200°C and the time is 1-5h.
8. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S4, the mass ratio of the pyrolysis product to polyvinyl pyrrolidone is 5-12:
1.
9. The method for preparing a low expansion silicon-carbon negative electrode material according to claim 1, characterized in that: In S4, heating is performed at 1200-1800°C and the temperature is maintained for 2-5 hours.
10. An application of a low expansion silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 9 is applied to the negative electrode of a lithium battery.
Citation Information
Patent Citations
Fluorine-free preparation method for three-dimensional porous silica powder anode material of lithium ion battery
CN102237519A
Preparation method of anode material compounding three-dimensional porous silicon doped titanium source with carbon
CN108376780A
Method for preparing carbon-coated porous silicon composite material
CN108963203A
Lithium ion battery porous silicon carbon nanosheet composite negative electrode material and preparation method thereof
CN110335998A
Method for preparing silicon-carbon negative electrode material through magnesiothermic reduction
CN111244414A